Economic growth in the Republic of Yemen : sources, constraints, and potentials (Washington, D.C. : World Bank, 2002)
The report is composed of three parts> Part 1 reviews economic performance in Yemen and assesses the government medium-and long-term development plan. Part II is devoted to the study of Yemen' private sector environment and external competitiveness given the importance accorded to the private sector and exports in the medium - and long-term development plans.
Includes bibliographical references (p. 107-109).
osc 2/09/2021
Loans
Keywords: Economic growth; Yemen (Republic); Yemen (Republic)